2009
DOI: 10.21608/eajbsa.2009.15440
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Spinosad, Lufenuron and Malathion against olive fruit fly, Bactrocera oleae (Gmelin) (Diptera: Tephritidae)

Abstract: Spinosad, Lufenuron and Malathion were evaluated in controlling olive fruit fly, Bactrocera oleae (Gmelin) under field conditions by using partial bait spray and killing bags during fruiting seasons of 2008 and 2009. The obtained results showed that the percentages of B. oleae populations and fruit infestation were obviously low in treated plots with Lufenuron, Spinosad and Malathion, respectively in comparison with control plot which were relatively high. The mean reduction percentages in B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Also, spinosad was effective on Mexican fruit fly especially to immature adults [58]. In addition, spinosad was more efficient than malathion in controlling Ceratitis capitata Wiedemann, B. zonata and B.oleae [29,59].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, spinosad was effective on Mexican fruit fly especially to immature adults [58]. In addition, spinosad was more efficient than malathion in controlling Ceratitis capitata Wiedemann, B. zonata and B.oleae [29,59].…”
Section: Discussionmentioning
confidence: 99%
“…This unique phenomenon occurs between insects and plant chemicals, which include lepidopterous insects-pyrrolizidine alkaloids [2], turnip sawflies-clerodendrins (triterpenoids) [3][4][5], diabroticite leaf beetles-cucurbitacins (triterpenoids) [3] and tephritid fruit fliesphenylpropanoids [3,6,7]. organophosphorous insecticides such as malathion, naled, dichlorvos and fenitrothionas the toxic component of attract and kill mixture [24][25][26][27][28][29][30]. Initial identification of spinosad as promising active insecticide for MAT purposes was reported previously [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dakahlia Governorate is a major agricultural area in northeast Egypt. In experiments with LFN sprays in the Aga region of Dakahlia, Moustafa et al () reported large reductions (86% in 2008 and 75% in 2009) in olive fly, B. oleae , populations after spraying orchards with LFN. LFN can also interrupt development and reproduction, mainly via its effects on cuticle in the medfly (Navarro‐Llopis et al., ; Navarro‐Llopis et al., ), in the mosquito, Aedes aegypti (Salokhe et al., ), in Drosophila melanogaster , and in other fly species (Mosson et al., ; Wilson and Cryan, ; Avila et al., ; Butter et al., ; Moya et al., ; Chang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, common insecticides such as dimethoate failed to protect olives for as long a period after the last spray. Research for biological control alternatives against this pest is based essentially on mass trapping methods and the use of natural product-based pesticides such as the Bacillus thuringiensis (Bt), spinosad that offer a more sustainable solution to pest control than synthetic alternatives (Lambert and Peferoen, 1992 [5]; Federici and Sakano, 2006 [6]; Sameh et al, 2009 [7]). Strategies involving semiochemical-based products have been pursued in the development of integrated pest management strategies for B. oleae (Mazomenos and Haniotakis, 1981 [8]; Gil-Ortiz, 2012 [9]; Canale et al, 2014 [10]).…”
Section: Introductionmentioning
confidence: 99%